Analisis Pengaruh Struktur Kepemilikan Saham Terhadap Nilai Perusahaan - Palangan, Milka (Universitas Sam Ratulangi, 2017)
The research objective is to examine the impact of the stock ownership structure to company value, which is divided in to 4 (four) classification that will be tested as follows : (1) stock ownership < 25%, (2) stock ownership between 25% - 50%, (3) stock ownership between 51% - 75%, and (4) stock ownership >75%. From this four classification that will be tested, there are only 2 (two) classification that is fit with the test because those two classification have the uniformity that fulfilled the condition to be tested as follows, there are (1) stock ownership between 25% - 50% and (2) stock ownership between 51% - 75%. This research uses regression analysis methodology to find out the relationshipÂ between independent variable and dependent variable with 3 (three) control variable as follows : total assets, total debts and total capital. Result of the researchÂ : (1) Stock ownership betweenÂ 25% - 50% have a significant effect to the company value if uses one of the control variable such as total asset or total debts or total capital. (2) Stock ownership between 51% - 75% do not have effect to the compnay value, with or without the control variablesKeywords: stock ownership structure, company value, banking